2020
DOI: 10.1093/cid/ciaa632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of 105 Hospitalized Patients With COVID-19 in Seattle, Washington

Abstract: Background Washington State served as the initial epicenter of the SARS-CoV-2 pandemic in the United States. An understanding of the risk factors and clinical outcomes of hospitalized patients with COVID-19 may provide guidance for management. Methods All laboratory-confirmed COVID-19 cases in adults admitted to an academic medical center in Seattle, WA between March 2 and March 26, 2020 were included. We evaluated individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
92
5
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 26 publications
13
92
5
5
Order By: Relevance
“…1); some studies reported data on > 1 pertinent outcome. Of these, there were 52 studies reporting results on obesity prevalence among patients with COVID-19 involving a total of 504,556 cases (8,9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (Table 2). There was signi cant evidence for heterogeneity across studies in all analyzes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1); some studies reported data on > 1 pertinent outcome. Of these, there were 52 studies reporting results on obesity prevalence among patients with COVID-19 involving a total of 504,556 cases (8,9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (Table 2). There was signi cant evidence for heterogeneity across studies in all analyzes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The retrieval publications were screened and abstracted if they met the following inclusion criteria: a) Observational studies (cohort, case-control, cross-sectional, case series); b) Studies providing su cient information for the calculation of relative risk (RR) and / or odds ratio (OR), in cases which critical data were not reported in the eligible articles, we contacted authors; c) Studies reporting the prevalence of obesity in COVID-19 patients (primary outcome) and/or data on the association between obesity and following secondary outcomes: COVID-19 and COVID-19 severity (severe COVID-19 was de ned based on international guidelines or hospitalization, ICU (Intensive Care Unit) admission, need for mechanical ventilator, mortality due to COVID-19 or a combination of these) (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Duplicates, case reports, reviews, studies with insu cient data after contacting with authors, and abstracts were all excluded, but letters were included.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Much of the modeling work related to the pandemic has focused on spread dynamics ( Kucharski et al, 2020 ). Others have described patients who were hospitalized ( Richardson et al, 2020 ) (n = 5700) and ( Buckner et al, 2020 ) (n = 105), became critically ill ( Gong et al, 2020 ) (n = 372), or succumbed to the disease (n = 1625 ( Onder et al, 2020 ), n = 270 [ Wu et al, 2020 ]). In data from the New York City, 14.2% required ICU treatment and 12.2% mechanical ventilation ( Richardson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once collected, respiratory specimens are most commonly analyzed in diagnostic laboratories by reverse transcription polymerase chain reaction (RT-PCR) to detect viral RNA 8,9 . Some RT-PCR tests are developed in-house, often following recommendations of reference laboratories and o cial institutions [10][11][12] . Other tests are commercially available and are in research use only (RUO) status or certi ed as invitro diagnostics (IVD) [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%